Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0118673
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Transcriptome Analysis of Oncomelania hupensis after Molluscicide Treatment by Next-Generation Sequencing: Implications for Biology and Future Snail Interventions

Abstract: The freshwater snail Oncomelania hupensis is the only intermediate host of Schistosoma japonicum, which causes schistosomiasis. This disease is endemic in the Far East, especially in mainland China. Because niclosamide is the only molluscicide recommended by the World Health Organization, 50% wettable powder of niclosamide ethanolamine salt (WPN), the only chemical molluscicide available in China, has been widely used as the main snail control method for over two decades. Recently, a novel molluscicide derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 31 publications
(36 reference statements)
1
23
0
Order By: Relevance
“…Based on Illumina RNA-seq analysis, Zhao et al (2015) described the responses of the amphibious snail, Oncomelania hupensis , after challenge with two different niclosamide-based molluscicides. They showed that two CYP genes and one GST gene were upregulated following molluscicide exposure [ 51 ]. This observation coupled with our results suggests that both enzyme families are a common component of the snail transcriptomic response to molluscicides.…”
Section: Discussionmentioning
confidence: 99%
“…Based on Illumina RNA-seq analysis, Zhao et al (2015) described the responses of the amphibious snail, Oncomelania hupensis , after challenge with two different niclosamide-based molluscicides. They showed that two CYP genes and one GST gene were upregulated following molluscicide exposure [ 51 ]. This observation coupled with our results suggests that both enzyme families are a common component of the snail transcriptomic response to molluscicides.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [15] undertook an Illumina-based study of the molluscicide-induced transcriptome of Oncomelania hupensis, the pomatiopsid snail host of S. japonicum. The response of B. pfeifferi to simultaneous exposure to schistosome infection and niclosamide exposure is the first glimpse we have for how snails respond transcriptionally to simultaneous exposure to these two relevant stressors.…”
Section: Resultsmentioning
confidence: 99%
“…CYPs are also up-regulated in B. pfeifferi in response to niclosamide exposure, including two in common with B. glabrata ( Table 1) Glutathione-S-transferase 7-like (GST) was up-regulated 5-fold following niclosamide exposure in B. glabrata [16]. In addition to CYPs, GST has also been shown to be upregulated following niclosamide-based molluscicide exposure in Oncomelania hupensis [15].…”
Section: Shared Response Of Two Biomphalaria Species To a Sublethal Dmentioning
confidence: 99%
“…By contrast, only a few study focused on the transcriptomic studies in the snail O. hupensis, for instance, Zhao et al have characterized the transcriptome profiling of O. hupensis from the two distinct habitats and identified thousands of genes that show either increased or decreased expression [15]. A RNA-Seq experiment revealed that gene expression of O. hupensis showed significantly effects exposed to two kinds of molluscicides [14]. Together these data demonstrate the highly dynamic nature of transcriptomic profile in response to environment, infection and molluscicide.…”
Section: Discussionmentioning
confidence: 99%
“…For O. hupensis, transcriptomic studies by RNA-seq have been performed after molluscicide treatment. Many genes involved in key processes associated with biological regulation and innate immunity have been identified, which would benefit for elucidating the molluscicidal mechanism [14]. Another study by comparing the differences in gene expression between the hilly and marshland snails revealed that there is a potential relationship between expression profiling and ecological adaptation of the snail that may have implications for schistosomiasis control in future [15].…”
Section: Introductionmentioning
confidence: 99%